Smart Contract Innovation and Blockchain-Based Tokenization in Higher Education - Gunawan, I Ketut; Lutfiani, Ninda; Aini, Qurotul; Suryaman, Fitria Marwati; Sunarya, Abas (Journal of Education Technology, 2021)
Blockchain which includes smart contract and tokenization features is the latest technology in the world, especially Indonesia. Smart contracts and tokenization make it very easy for users and can maintain valid data security, but there are still many universities that have not implemented the system so they have to involve many parties and costs. The problem taken in this study is the payment process for transactions such as credit and data processing that is vulnerable to illegal data leakage. This study aims to develop a smart contract system and blockchain tokenization in universities in the payment transaction process. The method used in this research is literature review analysis and testing method. The implementation of smart contracts and tokenization can replace third parties as security guards of transaction data with all Blockchain users paying attention and ensuring the integrity of the entire process and activity. This of course can avoid problems that arise from the presence of third parties in the transaction process. So it can be concluded that the implementation of smart contracts and Blockchain tokenization in payment transactions is the right solution to be applied in the payment transaction process at universities.